The effectiveness of a contractor development programme in the development of small contractors: an evaluation of a road construction project in the Eastern Cape - Mahlanga, Innocntia Nqobile (My University, 2018)
This research seeks to ascertain whether a Contractor Development Programme (CDP) has been beneficial to the development of fourteen (14) contractors enrolled within the programme. The investigation is conducted through an evaluation of a road construction project implemented by a State-Owned Enterprise (SOE) in the Eastern Cape Province in South Africa. This research considers the following factors in determining the effectiveness of the CDP: technical, financial and managerial training that the contractors received through the programme, the provision of relevant work experience for the duration of the programme as well as an increase in the contractor’s CIDB grading after exiting the programme. The study was motivated by the apparent lack of research reporting on the growth and sustainability of contractors having taken part in development programmes implemented by SOEs. The study found that the contractors received some training in technical, financial and managerial aspects. The contactors further received work experience and on-the-job training linked to the training programme. The study further found that even though all fourteen (14) enterprises have remained operational; after 4 years of having enrolled in the CDP, 71% of the contractors have remained at CIDB Grade 1 level. The study observes that the stagnation of the contractors’ CIDB grading, despite the contractors having been developed within a CDP, requires further investigation. Although the study focuses on one project where contractor development was implemented, the lessons and observations from the programme have broader relevance. The study further analyses the overall approach followed in implementing CDPs and emphasises some key considerations relating to the implementation approach. More importantly, the study highlights that the lack of emphasis on technical competence in terms of qualification and experience is one of the underlying shortcomings of CDPs. In conclusion, the research found that there is a need to review policies and procedures relating to CDPs.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, Johannesburg 2018
Keywords: Road construction industry--Economic aspects--South Africa; Roads--Maintenance and repair; Macadam roads--Design and construction